2018
DOI: 10.14814/phy2.13866
|View full text |Cite
|
Sign up to set email alerts
|

Dietary apple polyphenols increase skeletal muscle capillaries in Wistar rats

Abstract: Dietary apple polyphenols (AP) have been shown to exhibit beneficial effects on muscle endurance. Fast‐to‐slow change in the composition of myosin heavy chains was known as one of the molecular mechanisms. Here, we examined the effects of dietary AP on the capillaries and mitochondria in the rat skeletal muscle to elucidate the mechanisms underlying muscular endurance enhancement. Twenty‐four Wistar male rats were divided into three groups, namely, the control group, 0.5% AP group, and 5% AP group (n = 8 in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Here, we investigated the effect of dietary APPs supplementation on lipid metabolism in weaned piglets. We found that dietary APPs supplementation had no effect on growth performance, which is consistent with previous reports (Manzano et al, ; Nakazato et al, ; Yoshida et al, ). On the contrary, some other investigations based on mouse model of hyperlipidaemia or rats fed cholesterol showed different response patterns (improvement or decrease in growth performance; Osada et al, ; Xu et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Here, we investigated the effect of dietary APPs supplementation on lipid metabolism in weaned piglets. We found that dietary APPs supplementation had no effect on growth performance, which is consistent with previous reports (Manzano et al, ; Nakazato et al, ; Yoshida et al, ). On the contrary, some other investigations based on mouse model of hyperlipidaemia or rats fed cholesterol showed different response patterns (improvement or decrease in growth performance; Osada et al, ; Xu et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Protein extraction and Western blot analysis. Muscle samples were homogenized as previously described (53,62), using RIPA buffer (188-02453; Fujifilm Wako Pure Chemical, Osaka, Japan) containing protease and phosphatase inhibitor cocktail (169-26063/167-24381, Fujifilm Wako Pure Chemical). Protein concentrations of the samples were measured using the Lowry method (DC protein assay, Bio-Rad, Hercules, CA).…”
Section: Ethical Approvalmentioning
confidence: 99%
“…Previous studies reported the ability of polyphenols to improve exercise capacity and endurance in rats. According to previous studies, these effects may be due to role of polyphenols in both reductions of OxS in muscle and improvement of the vascular and endothelial function [37][38][39], resulting in a global amelioration of the skeletal muscle health.…”
Section: Discussionmentioning
confidence: 96%